2014
DOI: 10.1016/j.jbi.2014.08.004
|View full text |Cite
|
Sign up to set email alerts
|

LabeledIn: Cataloging labeled indications for human drugs

Abstract: Drug-disease treatment relationships, i.e., which drug(s) are indicated to treat which disease(s), are among the most frequently sought information in PubMed®. Such information is useful for feeding the Google Knowledge Graph, designing computational methods to predict novel drug indications, and validating clinical information in EMRs. Given the importance and utility of this information, there have been several efforts to create repositories of drugs and their indications. However, existing resources are inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 26 publications
0
41
0
Order By: Relevance
“…28,29 Hypertension medications were determined using medication strings with indications determined as part of MedicationIndication resource-High Performance Subset (MEDI-HPS), which lists on-and off-label indications of medications (Supplemental Table 3). [30][31][32][33] We used the hypertensive blood pressure guideline thresholds of 140 mmHg systolic and 90 mmHg diastolic. We separated vital readings into outpatient and inpatient only and collapsed multiple daily readings to their median values.…”
Section: Input Feature Developmentmentioning
confidence: 99%
“…28,29 Hypertension medications were determined using medication strings with indications determined as part of MedicationIndication resource-High Performance Subset (MEDI-HPS), which lists on-and off-label indications of medications (Supplemental Table 3). [30][31][32][33] We used the hypertensive blood pressure guideline thresholds of 140 mmHg systolic and 90 mmHg diastolic. We separated vital readings into outpatient and inpatient only and collapsed multiple daily readings to their median values.…”
Section: Input Feature Developmentmentioning
confidence: 99%
“…Towards such a goal, we recently created LabeledIn ( 27 ) based on manual curation of drug labels. To accelerate the manual curation process, we adopted a semiautomated pipeline where all disease occurrences are first tagged by a text-mining tool.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Duke et al (2013) demonstrated the dangers of using drug labels as an ADR KB by identifying numerous inconsistencies between the labels for bioequivalent drugs. Meanwhile, drug indications (i.e., the medical condition the drug is intended to treat) have also been well-studied (Névéol and Lu, 2010;Fung et al, 2013;Khare et al, 2014), as have drug interactions (Demner-Fushman et al, 2018a). All of these focus on general aspects of a drug, while hardly any work has focused on the information in drug labels related to specific populations, though both the TAC task as well as Culbertson et al (2014) identified ADRpopulation relations.…”
Section: Drug Label Information Extractionmentioning
confidence: 99%